TECHNOLOGICAL ADVANCEMENT AND AI USAGE ON INTERPRETING TEACHING: A LECTURER’S PERSPECTIVES - Firhan Hidayat; Eka Nurhidayat; Rahma Ilyas (Cirebon International Conference on Education and Economics Proceeding, 2024)
Advancements in interpreting technology have significantly enhanced cross-language communication. This study examines how interpreting lecturers introducing their students to utilize these technologies in the classroom. It also explores the lecturers’ personal perspectives on AI and interpreting tools. Using a qualitative approach, this study involved purposive sampling of two interpreting instructors who are also professional interpreters. The data for this study collected by conducting open ended interviews, followed by observing the method used to introduce the interpreting tools and how the sample’s students perceive it. The findings indicate that interpreting tools are currently introduced merely as supporting aids and its usage are not yet fully integrated into the curriculum. The lecturers also believe that AI and interpreting tools are not yet be able to replace the needs of human interpreter. They also support for the measured introduction of these tools to students, considering ethical implications, optimal usage, and avoiding counterproductive practices in student learning.